Emotional intelligence function to predict the decision to take the first-class futsal referees - Saeed, Husam (Journal of Physical Education, 2015)
The study aimed to identify the level of use of knowledge management and information technology at the administrative leadership Came the main objectives of the research are as follows : 1. Find out the relationship between emotional intelligence and decision-making of the sample in question. 2. determine the proportion of the contribution of emotional intelligence in the decision-making of the sample in question. 3. predict the decision-making of the sample in question in terms of emotional intelligence .To achieve those goals use researcher descriptive approach - style survey and study the correlation relations - as represented search tools sample of the first class of the game Futsal rulers ( of the 60 ) judgment , as well as measurements of ( emotional intelligence , decision-making ) , .. After a series field procedures to make sure of the validity of the two scales , by ensuring that the terms of the psychometric characteristics ( honesty, fortitudeBegan researcher conducted a major experiment - the application of the two scales - and the use of appropriate statistical methods , and using statistical bagful (spss) for data processing and show the results in order to serve the research and achieve goals, the researcher suggested that the decision-making among a sample search is linked to the relationship of the fact that a function with emotional intelligence and emotional intelligence It contributes a large margin in the decision-making , and thus devised a researcher predictive equation by which to predict the decision-making of the sample in terms of emotional intelligence